(untitled) (Medical Forum Monthly, 2021)
Objective: To characterize the obstetrical management and maternal outcomes in a series of women presenting with placenta previa and placenta accrete spectrum disorders in pregnancy. Study Design: Prospective case series Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Shaikh Zayed Hospital, Lahore from January 2018 to December 2020 for a period of one year. Materials and Methods: Twenty-five women age between 27-39 years who were prenatally diagnosed with placenta previa with placenta accreta spectrum disorders through ultrasound and/or magnetic resonance imaging were included. All patients underwent caesarean hysterectomy. The hospital stay, post-operative maternal and neonatal outcomes were recorded. Results: The mean age was 34.9±5.1 years and mean gestational age at delivery was 36.3±1.3 weeks. The average blood loss in women was 3.5 litres. All women had placenta previa but 12 had placenta accreta while rest had placenta increta and percreta. Two previous caesarean histories were noticed in 82.04% and of ≥3 in 5.30% patients. Conclusion: Massive blood loss, caesarean hysterectomy and pre-term delivery were evident outcomes of placenta previa with placenta accreta spectrum disorder. The incidence of prior caesarean sections was high among these patients.